Surgical, histopathological, and clinical outcomes of parotid gland neoplasms: a 10-year tertiary single-center experience - Aliyeva, Aynur; Yagız Agayarov, Ozlem; Aksoy Yıldırım, Gökçe; Muderris, Togay; Dalgıc, Abdullah (The European Research Journal, 2023)
Objectives: This study aims to contribute to the literature by presenting an overview of a 10-year experience by retrospectively examining the cases with a parotid mass from a tertiary referral center Methods: Two hundred fourteen patients were diagnosed with a parotid mass in the Otorhinolaryngology Clinic of HSU Izmir Bozyaka Training and Research Hospital between January 2009 and January 2019. Sociodemographic characteristics, diagnostic methods, surgical operations and complications, pathology results, and long-term follow-up results were retrospectively analyzed over the patients’ files. SPSS Version 21.0 computer for data analysis. Results: Of 214 parotidectomies, 140 (75%) were male, 74 (35%) were female, mean age was 55 ±14 years (15-85 years). The most common diagnoses were 87 (40.7%) pleomorphic adenomas and 48 (22.4%) Wharton tumors. The most prevalent malignant tumors were reported as 18 (8.1%) mucoepidermoid carcinoma. The main type of surgery was superficial parotidectomy, performed in 192 (90%) patients. Facial paralysis was observed in 11 (5.1%) patients as the main postoperative complication. Conclusions: Considering the histopathological diagnosis of parotid tumors, the stage and grade of the tumor, surgery is generally preferred for treatment. More males are affected than women, especially in the middle ages.